City Folk : English Country Dance and the Politics of the Folk in Modern America. - Walkowitz, Daniel J. (NYU Series in Social & Cultural Analysis., 2010)
This is the story of English Country Dance, from its 18th century roots in the English cities and countryside, to its transatlantic leap to the U.S. in the 20th century, told by not only a renowned historian but also a folk dancer, who has both immersed himself in the rich history of the folk tradition and rehearsed its steps. In City Folk, Daniel J. Walkowitz argues that the history of country and folk dancing in America is deeply intermeshed with that of political liberalism and the 'old left.' He situates folk dancing within surprisingly diverse contexts, from progressive era reform, and p.